Development of Learning Videos with the Kinemaster Application to Facilitate Online Learning at Junior High Schools in Aceh Besar - Syarifah Farissi Hamama; Maulida Maulida (STAI Hubbulwathan Duri, 2022)
The teaching and learning process which is usually conducted face-to-face has been turned into an online learning process because the whole world is experiencing the covid 19 pandemic. Online learning is not without challenges, there are so many challenges that are faced during the learning process. The purpose of this research is to create learning media using the Kinemaster application to facilitate online learning. The research starts from the preparation of the proposal in June 2020 until March 2021. The length of time to conduct this research is 3 months. The method used in this research is R D (Research and Development). The learning media testing involves 3 experts (media experts, linguists, concept experts/experts in developing teaching materials). The results show that learning media with the Kinemaster application can already be applied, based on the validation test 81,94%. These results refer to the validity of the media carried out by the experts involved in the research. The result validity category is quite valid, which means, it can be used but needs minor revisions. Revisions are made based on the results of the validator’s input and suggestions both directly, responses and suggestion given in writing on the validation sheet.